(untitled) (Journal of Current and Advance Medical Research, 2018)
Background: There are several etiologies of urinary tract obstructions. Objective: The purpose of the present study was to find out the etiology of urinary tract obstructions. Methodology: This cross-sectional study was conducted in the Department of Surgery at Rajshahi Medical College, Rajshahi, Bangladesh from September 1994 to December 1995 for a period of one year and three months. All the patients who were presented with bladder outflow obstruction and were admitted in the general surgical unit of the hospital were taken as study population. Result: A total number of 50 patients were recruited for this study. The most frequent cause of bladder outflow obstruction was benign enlargement of prostate (26.0%), next common cause was impacted urethra stone (22.0%) and stricture urethra (22.0%). Rupture urethra was found in 7(14.0%) cases and carcinoma of prostate was found in 3(6.0%) cases. Conclusion: In conclusion the most frequent cause of bladder outflow obstruction is benign enlargement of prostate, impacted urethra stone and stricture urethra. Journal of Current and Advance Medical Research 2018;5(1):3-6